Improving News Text Writing Skills Using Photo Story Media for Junior High School Students - Jumriati; Andi Wiwiek Winati; Dwi Syukriady (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2026)
This study aims to improve news text writing skills through the use of photo story media in class VII-1 students of SMP Negeri 36 Makassar. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects were 32 students, consisting of 15 male students and 17 female students. Data collection techniques were carried out through tests and non-tests in the form of observation, questionnaires, and documentation. Data were analyzed quantitatively and qualitatively. The results of the study indicate that the use of photo story media can improve students' news text writing skills. This can be seen from the increase in students' average scores, namely from 37.56% in cycle I to 71.34% in cycle II. In addition, student activity and participation in the learning process also increased. Students became more active, more focused on paying attention to teacher explanations, more enthusiastic in asking questions, and calmer when participating in the learning process and doing assignments. Thus, this study can conclude that photo story media is effectively used to improve news text writing skills of class VII-1 students of SMP Negeri 36 Makassar.